A scanning electron microscopical study of initial changes in human premolars teeth after orthodontic tooth movement (Mustansiria Dental Journal, 2024)
scanning electron microscope was used to study the effect of orthodontic tooth movement by using a force of 50 grams on the pressure side of 2l upper left premolarmt for 5- 75 days while the contralaterl side 14 teeth were used as a control. In order toruiy the morphology and occurrence of root resorptions, the organic tissue was removedrsigg sodium hypochlorite and the denuded root surface were re—examined in thescanning electron microscope. Initially, tissue affected by pressure was mainly located inhe marginal region and subsequently the mid- portion of the roots became generallyuri genced. The resorption process of cementum begins after 5 days as around cavitiesmeasuring about 4u. Further resorption in cementum was characterized by measuringsmall, thin—walled round lacunae which confluence into extensive, shallow resorptionsafter 25 days and more